SIMULASI ANALISIS VELOCITY ALIRAN FLUIDA PADA TANGKI REAKTOR NUKLIR MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMICS (CFD) - Mifta Aroyyani; Agus Nuramal; Hendri Hestiawan (UNIB Press, 2022)
Center for Applied Nuclear Science and Technology (Pusat Sains dan Teknologi Nuklir Terapan /PSTNT) is a work unit that is under and directly responsible to the Deputy for Nuclear Science and Applications of Nuclear Technology, National Nuclear Energy Agency. In PSTNT Bandung, the function of the tank is as a container to place the reactor components, the reactor shield for the heat exchanger and as a place for nuclear reactions to take place. In nuclear reactor tank flow distribution ocures in various velocity.The purpose of this practical work is to analyze the velocity of fluid flow in the reactor tank from the inlet flow to the bottom surface of the reactor and from the bottom surface to the top surface of the TRIGA 2000 reactor. The method used in this practical work is the Computational Fluid Dynamics (CFD) Velocity method. CFD is a method for simulating fluid flow. The method is processed numerically and then digitally modeled. In practice, the authors modeled and studied the conceptual design of the reactor system using CFD based on Gambit and Fluent applications in a reactor tank. GAMBIT is an application produced by fluent inc. which is useful for making a model and discrete (meshing) to be analyzed by numerical methods. Fluent is an application that can solve fluid flow cases with the results obtained after discretizing the GAMBIT application. The results by CFD shows the distribution of fluid flow from the inlet pipe to the bottom surface of the reactor tank then the flow rises to the top surface to the outlet pipe. The velocity of the fluid flow from the inlet flow to the bottom surface was getting smaller, and the smallest value was at the bottom of the nuclear reactor, by 0.164 m/s and the flow distribution from the bottom surface to the top surface of the velocity value in a nuclear reactor would be bigger by the largest value being on the top surface of the nuclear reactor is 2.9 m/s.